2018
DOI: 10.1001/jama.2018.13770
|View full text |Cite
|
Sign up to set email alerts
|

Association of Thyroid Hormone Therapy With Quality of Life and Thyroid-Related Symptoms in Patients With Subclinical Hypothyroidism

Abstract: The benefit of thyroid hormone therapy for subclinical hypothyroidism is uncertain. New evidence from recent large randomized clinical trials warrants an update of previous meta-analyses. OBJECTIVE To conduct a meta-analysis of the association of thyroid hormone therapy with quality of life and thyroid-related symptoms in adults with subclinical hypothyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
165
1
8

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 208 publications
(180 citation statements)
references
References 68 publications
6
165
1
8
Order By: Relevance
“…As shown in Tables 1 and 2 of 29 (6.9%) included metaanalyses, both published in specialty journals [34,43], reported receiving pharmaceutical industry funding, 11 (37.9%) reported non-industry funding [23, 26, 29-32, 35, 40, 49-51], 3 reported no study funding (10.3%) [28,33,46], and the funding source of 13 (44.8%) was not reported [24, 25, 27, 36-39, 41, 42, 44, 45, 47, 48]. Meta-analysis funding sources were reported for 8 of 11 meta-analyses from general medicine journals (72.7%) [23,26,[28][29][30][31][32][33], 5 of 15 (33.3%) from specialty medicine journals [34,35,40,43,46], and all 3 (100%) Cochrane reviews [49][50][51].…”
Section: Study Funding and Author-industry Financial Ties Of Metaanalmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Tables 1 and 2 of 29 (6.9%) included metaanalyses, both published in specialty journals [34,43], reported receiving pharmaceutical industry funding, 11 (37.9%) reported non-industry funding [23, 26, 29-32, 35, 40, 49-51], 3 reported no study funding (10.3%) [28,33,46], and the funding source of 13 (44.8%) was not reported [24, 25, 27, 36-39, 41, 42, 44, 45, 47, 48]. Meta-analysis funding sources were reported for 8 of 11 meta-analyses from general medicine journals (72.7%) [23,26,[28][29][30][31][32][33], 5 of 15 (33.3%) from specialty medicine journals [34,35,40,43,46], and all 3 (100%) Cochrane reviews [49][50][51].…”
Section: Study Funding and Author-industry Financial Ties Of Metaanalmentioning
confidence: 99%
“…As shown in Table 3, 13 of 29 (44.8%) meta-analyses reported the funding sources of included RCTs; 12 reported for all included RCTs [23,24,26,27,29,30,32,34,45,[49][50][51], whereas 1 reported for 5 of 7 included RCTs [39]. Funding sources of included RCTs were reported for 7 of 11 (63.6%) meta-analyses from general medicine journals [23,24,26,27,29,30,32], 3 of 15 (20.0%) from specialty medicine journals [34,39,45], and for all 3 (100%) Cochrane reviews [49][50][51]. The mean, median, and range of the number of RCTs in meta-analyses that reported trial funding sources were 52.9, 13, and from 2 to 522, respectively.…”
Section: Reporting Of Trial Funders and Author Fcoi From Rcts Includementioning
confidence: 99%
“…The results, reported in JAMA ,1 showed that thyroid hormone therapy (for 3-18 months) was associated with reducing the mean thyrotropin value into the normal reference range when compared with placebo (range 0.5-3.7 mIU/L v 4.6-14.7 mIU/L). But no improvement was found in thyroid related symptoms or quality of life.…”
mentioning
confidence: 98%
“…Thyroid function tests, included as part of the Quality and Outcomes Framework, saw a 7.1% average annual increase over the study period 2. A proportion of people tested will receive a diagnosis of subclinical hypothyroidism,7 which is often treated with thyroid hormones, especially when it co-occurs with symptoms potentially attributable to hypothyroidism, such as fatigue and weight gain 8. A recent systematic review and meta-analysis of 21 randomised controlled trials, however, reported that thyroid hormone treatment was not statistically significantly associated with improvements in quality of life or thyroid related symptoms for people with subclinical hypothyroidism 7.…”
mentioning
confidence: 99%
“…A proportion of people tested will receive a diagnosis of subclinical hypothyroidism,7 which is often treated with thyroid hormones, especially when it co-occurs with symptoms potentially attributable to hypothyroidism, such as fatigue and weight gain 8. A recent systematic review and meta-analysis of 21 randomised controlled trials, however, reported that thyroid hormone treatment was not statistically significantly associated with improvements in quality of life or thyroid related symptoms for people with subclinical hypothyroidism 7. This is an example of overmedicalisation, where a patient might be treated for a laboratory abnormality without clinical benefit but with attendant risks of side effects as well as the practical inconvenience.…”
mentioning
confidence: 99%